The American way of bombing : changing ethical and legal norms, from flying fortresses to drones - Evangelista, Matthew, 1958-; Shue, Henry; Biddle, Tami Davis, 1959- (Cornell University Press, 2014)
Aerial bombardment remains important to military strategy, but the norms governing bombing and the harm it imposes on civilians have evolved. The past century has seen everything from deliberate attacks against rebellious villagers by Italian and British colonial forces in the Middle East to scrupulous efforts to avoid "collateral damage" in the counterinsurgency and antiterrorist wars of today. The American Way of Bombing brings together prominent military historians, practitioners, civilian and military legal experts, political scientists, philosophers, and anthropologists to explore the evolution of ethical and legal norms governing air warfare. Focusing primarily on the United States--as the world's preeminent military power and the one most frequently engaged in air warfare, its practice has influenced normative change in this domain, and will continue to do so--the authors address such topics as firebombing of cities during World War II; the atomic attacks on Hiroshima and Nagasaki; the deployment of airpower in Iraq, Afghanistan, and Libya; and the use of unmanned drones for surveillance and attacks on suspected terrorists in Pakistan, Yemen, Sudan, Somalia, and elsewhere. Contributors: Tami Davis Biddle, U.S. Army War College; Sahr Conway-Lanz, Yale University Library; Neta C. Crawford, Boston University; Janina Dill, University of Oxford; Charles J. Dunlap Jr., Duke University; Matthew Evangelista, Cornell University; Charles Garraway, University of Essex; Hugh Gusterson, George Mason University; Richard W. Miller, Cornell University; Mary Ellen O'Connell, University of Notre Dame; Margarita H. Petrova, Institut Barcelona d'Estudis Internacionals; Klem Ryan, United Nations, South Sudan; Henry Shue, University of Oxford